2014
DOI: 10.1590/s1516-05722014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de fungos micorrízicos arbusculares na bioprodução de fenóis totais e no crescimento de Passiflora alata Curtis

Abstract: Os compostos fenólicos encontrados no extrato das folhas de maracujazeiro doce (Passiflora alata Curtis) são os principais responsáveis pelos efeitos terapêuticos, incluindo a atividade ansiolítica. O presente trabalho avaliou o efeito de diferentes espécies de fungo micorrízicos arbusculares (FMAs) e doses de fósforo sobre a bioprodução de fenóis totais, bem como, o crescimento vegetal e os conteúdos de nitrogênio, fósforo e potássio na massa da matéria seca da parte aérea do maracujazeiro doce. O experimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…The increase in plant height, number of leaves, and dry mass weight of shoots and roots in plants from AMF treatments may be due to the increase in P and K contents, which was higher than those observed in plants from the inoculation control treatment, at all evaluated N dosages. Similar results have been obtained in sweet passionfruit by Riter Netto et al (2014).…”
Section: Discussionsupporting
confidence: 89%
“…The increase in plant height, number of leaves, and dry mass weight of shoots and roots in plants from AMF treatments may be due to the increase in P and K contents, which was higher than those observed in plants from the inoculation control treatment, at all evaluated N dosages. Similar results have been obtained in sweet passionfruit by Riter Netto et al (2014).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, Riter Netto et al [19] developed a study using screens and reported an increase in the foliar content of total phenols in Passiflora alata Curtis inoculated with C. etunicatum , Rhizophagus intraradices , and mixed inoculum ( Rhizophagus clarus and Gigaspora margarita ) in relation to the non-inoculated control. Other field studies that differ from ours indicate that inoculation with AMF provided an increase in these compounds, as recorded in flowers of Cynara cardunculus L. var.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of biomolecules of the secondary plant metabolism in response to symbiosis may be attributed to mechanisms as the improvement of the nutritional condition of the host [18, 19], activation of metabolic routes [21], production of signaling molecules [20], alterations in the activity of key-enzymes for the production of these compounds [20], hormonal alterations [45], increase in the expression of genes involved in the biosynthesis of these biomolecules [22, 45]. Such mechanisms have also been suggested in other studies [8, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to the preparation of these seedlings is to use AMFs, which have contributed to reduce the production time of several fruit trees such as citrus (Altoé et al, 2008), yellow passion fruit (Cavalcante et al, 2001;Cavalcante et al, 2002), sweet passion fruit (Anjos et al, 2005;Vitorazi et al, 2012), papaya (Lima et al, 2011) and cashew (Weber et al, 2004), in addition to reducing phosphate fertilization (Riter Netto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%